GE_GERICHTE C/13577/2001 vom 16. Dezember 2008 - GE Cour de justice (2008)
GÉRANT DE FORTUNE ; BANQUE DÉPOSITAIRE; CONCOURS DE RESPONSABILITÉS; CESSION DE CRÉANCE(CO) | CO.164.1 CO.50.2 CO.51 LPC.181.3